2020
DOI: 10.1101/2020.06.16.151704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massive transient damage of the olfactory epithelium associated with infection of sustentacular cells by SARS-CoV-2 in golden Syrian hamsters

Abstract: Anosmia is one of the most prevalent symptoms of SARS-CoV-2 infection during the COVID-19 pandemic. However, the cellular mechanism behind the sudden loss of smell has not yet been investigated. The initial step of odour detection takes place in the pseudostratified olfactory epithelium (OE) mainly composed of olfactory sensory neurons surrounded by supporting cells known as sustentacular cells. The olfactory neurons project their axons to the olfactory bulb in the central nervous system offering a potential p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
145
0
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(181 citation statements)
references
References 28 publications
13
145
0
20
Order By: Relevance
“…The pathogenicity of SARS-CoV2 in the nasal cavity of the hamsters infected in this study involved respiratory and olfactory epithelium, including sustentacular cells (17). In ferrets, similar infection pattern has also been observed (9).…”
Section: Discussionsupporting
confidence: 69%
“…The pathogenicity of SARS-CoV2 in the nasal cavity of the hamsters infected in this study involved respiratory and olfactory epithelium, including sustentacular cells (17). In ferrets, similar infection pattern has also been observed (9).…”
Section: Discussionsupporting
confidence: 69%
“…There is now an emerging consensus that mature olfactory neurons do not express the virus entry proteins, ACE2 and TMPRSS2, at least not at significant levels, and not in the large majority of the mature olfactory neurons in mouse and human (Baxter and others 2020; Bilinska and others 2020; Brann and others 2020; Chen and others 2020b; Fodoulian and others 2020; Gupta and others 2020; Klingenstein and others 2020; Ziegler and others 2020-see Table 2). A recent study that localized the SARS-CoV-2 virus in the hamster olfactory epithelium confirmed this notion by showing that sustentacular cells contained the virus, but not olfactory neurons (Bryche and others 2020). This means that the olfactory neurons are not the initial and primary target of the virus.…”
Section: Anosmia In Covid-19: What Is the Underlying Mechanism?mentioning
confidence: 91%
“…Further studies are warranted to determine what factors are necessary and sufficient for viral egress and could therefore serve as potential therapeutic targets. Multiple groups have demonstrated success using golden Syrian hamsters to model SARS-CoV-2 infection, pathogenesis, and possibly transmission[35,[52][53][54], which may reflect differing susceptibility of hamster cell types based on anatomical location of the isolated cells.…”
mentioning
confidence: 99%